Perubahan Fungsi Paru pada Usia Tua: [Lung Function Alteration in Geriatric Patients] - Helmia Hasan; Rena Arusita Maranatha (Jurnal Respirasi, 2017)
Aging causes many changes in biological processes characterized by progressive and widespread changes associated with increased susceptibility to various diseases. Aging is not a homogeneous process. In contrast, human organs aging at different rates are affected by several factors, including genetic factors, lifestyle, and environmental exposure. Healthy aging remains accompanied by some morphological and functional changes in the respiratory system. During the first two decades of life, the lungs undergo a phase of growth and maturation. Respiratory system achieves maximum function at the age of 20 years for women and 25 years for men. Throughout the rest of life, aging is associated with a progressive decline in pulmonary performance and function. The normal aging of the respiratory system is associated with structural and functional decline in the respiratory system, resulting in increased respiratory work compared to younger subjects and is associated with reduced reserves in cases of acute illness, such as heart failure, infection, or airway obstruction. Pulmonary function decreases slowly throughout life even in healthy people. Disabilities and diseases related to aging are a global problem due to the longevity of life expectancy. An increased proportion of the elderly population is a challenge for doctors because of the clinical complexity of the elderly. A better understanding of change can help diagnose and treat lung disease in the elderly population.